DESAIN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Sholihah Sholihah (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Islamic Education Curriculum is designed to increase the students' faith and devotion to Allah SWT and the formation of noble morality. Faith, devotion and morality could expectedly be achieved through Islamic Religious Education by firstly encouraging the students to have the knowledge and understanding comprehensively related to the teachings of Islam and be capable of carrying it out properly. Thus the Islamic Education curriculum should be able to deliver students to the knowledge and understanding that are balanced between the acquisition of knowledge about Islam and the ability of implementing the teachings and developing the values of noble morality. To explore the substance of this curriculum, the writer will do more in-depth explanation of the curriculum as subject centered design, learner centered design, and problem centered design.Keywords: Design development, curriculum, Islamic religious education